Combat Service and Posttraumatic Stress Disorder as a Violent Crimes Predictor in OEF/OIF Veterans - Ivory, Rachel L. (2017)
There is an established link between posttraumatic stress disorder (PTSD) and criminal activity. Of every 100 veterans who served during Operation Enduring Freedom (OEF)/Operation Iraqi Freedom (OIF), 11 to 20 percent are diagnosed with PTSD each year. Previous research has documented that veterans are incarcerated at higher percentages compared to nonveteran inmates, though little published research examines incidence of PTSD relative to violent crime. Using Agnew's general strain theory as the foundation, the purpose of this correlational study was to examine combat service, PTSD, and specific violent crimes as defined by the FBI as murder and nonnegligent manslaughter, forcible rape, robbery, and aggravated assaults; while controlling for branch of service, age, and sex. The sample consisted of 46 OEF/OIF inmates (federal and state) 9 of whom were convicted of a violent crime. Results from the multiple logistic regression analysis showed that combat service, PTSD, sex, and branch of service were not statistically significant predictors of imprisonment of OEF/OIF veterans for violent crime. Age, however, was statistically significant p = .029. The findings of this study contribute to social change by providing policymakers and prison administrators nuanced information (i.e., characteristic information - age, sex, branch of service, etc.) about the needs of this unique prison population with regards to reintegration. This may in turn contribute to improved reintegration initiatives to enrich the lives of veterans, their families, and the communities where veterans reside when returning from war. Focusing on reintegration will be very beneficial